Предмет: Алгебра,
автор: udotmaltsev
докажите тождества (a-b)(a+b)-a(a-b)=b(a-b)
Ответы
Автор ответа:
1
Ответ:
Объяснение:
(a-b)*(a+b)-a*(a-b)=b*(a-b)
По формуле разности квадратов получаем, что (a-b)*(a+b) = a^2 - b^2, где ^ - степень.
a^2 - b^2 - a^2 + ab = ba - b^2
Перенесём всё в левую часть:
-b^2 + ab - ba + b^2 = 0
0 = 0 - Истина
Похожие вопросы
Предмет: Биология,
автор: fanedisonpt
Предмет: Геометрия,
автор: ghdjdhdhsjeh
Предмет: Биология,
автор: fanedisonpt
Предмет: Математика,
автор: Ami131313
Предмет: История,
автор: Anni768